Adolescent predictors of female dating violence perpetration. Issue 1 (2nd January 2017) - King, Dione Moultrie; Hatcher, Schnavia Smith; Bride, Brian
ABSTRACT: Teen dating violence is a significant problem impacting the adolescent experience with adolescent females at-risk to perpetrate violence. The National Longitudinal Study of Adolescent Health ( Add Health ) was used to assess perpetration risk behaviors through an examination into adolescent behaviors that shape their dating experiences. This study examined adolescent female perpetration of dating violence and the associations between alcohol use, racial identification, and delinquency using a nationally representative longitudinal sample. It was hypothesized that both models would predict dating violence perpetration based on prior knowledge and research studies that have been conducted among adolescent samples. Although risk behaviors were present among adolescents in this nationally representative sample, threats of violence and physical perpetration of violence were reported at levels lower than hypothesized. The findings of this study identified adolescent female minorities as being at an increased risk to perpetrate physical dating violence. These findings demonstrate the continued need to examine female perpetration of dating violence and incorporate these experiences in prevention and intervention efforts.